Association of P wave Dispersion with Angiographic Severity in Patients with Chronic Stable Angina - Islam, Syed Nazmul; Ahsan, Syed Ali; Mahmood, Manzoor; Adhikary, Dipal Krishna; Ahmed, Khurshed; Sultana, Syeda Niger; Nahar, Jannatun; Siddiki, Kamruzzaman; Siraj, Mohamed Mausool; Rahman, Abu Taher Mohammed Zubair; et al. (University Heart Journal, 2021)
Background:Stable angina forms a significant proportion of coronary artery disease. Newer non-invasive modalities with good predictive values like CT coronary angiography and myocardial perfusion imaging are available, they are not feasible for widespread use. In this scenario, we can use the ECG parameter (P wave dispersion) as a non-invasive, efficient and cost-effective tool for diagnosing coronary artery stenosis in chronic stable angina. Objective: To find out the association between P wave dispersion in electrocardiogram and angiographic findings by coronary angiogram in patients with chronic stable angina. Methods: This cross sectional study was conducted at the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2018 to June 2019.Patients with chronic stable angina who were undergoing invasive coronary angiography was included in this study. A total of 45 patients were included in the study. Immediately after admission, standard 12 lead ECG was recorded at a 50 mm/s paper speed and a gain of 10 mm/mV. P wave dispersion are calculated from the standard ECG during sinus rhythm in any of the 12 ECG leads. Finally, all the enrolled patients underwent invasive evaluation by coronary angiography. The severity of CAD was assessed by Gensini score. Results:The mean PD was 23.3±8.1 millisecond in patients without CAD, 37.1±7.6 millisecond in single vessel disease, 45.3±9.1 millisecond in double vessel disease and 45.9±9.4 millisecond in triple vessel disease, which were statistically significant (p<0.05) among four groups.There was a significant correlation of PD (P wave dispersion) with Gensini score (r=0.631; p=0.001). Conclusion: This study demonstrates that there is a significant association of PD (P wave dispersion) with the severity of coronary artery disease in patients with chronic stable angina. University Heart Journal Vol. 17, No. 2, Jul 2021; 81-85